INSURANCE AS A GUARANTEE OF COMPENSATION OF LOSS AND DAMAGES TO PROPERTY - О. В. Слободянюк; Г. В. Толкачева (Ринкова економіка: сучасна теорія і практика управління)
The problem of forming of a strong insurance market is critical to address the domestic economy. By providing the services through insurance coverage insurance companies reduce the financial risk of entities and generate significant amounts of investment resources to finance the national economy. Citizens property insurance is an essential component in ensuring the social protection of both individuals and legal entities and improving their welfare. Therefore, the improvement of property insurance and its impact on the domestic insurance market is a key issue today. The article is a study of theoretical principles of disclosure of economic essence of property insurance in the current market conditions and clarifying major issues of property insurance in Ukraine. The following methods were used in the study: systematic approach, theoretical generalization and comparison, analysis and synthesis.Property insurance - is the insurance industry, which is the object of the insurance relationship of property interests that do not contradict the legislation of Ukraine related to the possession, use and disposal of property of legal entities or individuals which shall be based on voluntary agreement concluded between the insurer and insurer. In a market economy, insurance industry plays an important role in society.The main problems that hinder the development of property insurance in Ukraine are: low level of household income level, low level of insurance culture, decrease of insurance payments from insurance companies to reduce the number of concluded contracts, breach of obligations by some insurers, the release of a significant number of staff in the insurance market, the inability to return the insurance reserves that have been placed on deposit accounts in banks due to the crisis and others. However, these problems are not fully affect the development of the insurance market in property insurance and is proving to review statistical data for the past periods of insurance companies. Directions for improvement of this type of insurance can be: clear regulation of organizational and economic issues of property insurance; development of transparent and acceptable rules of property insurers scope of insurance services; increase financial stability and sustainability performance of insurance companies; conduct research study on staff development insurers and insurance brokers. For further developments in the field of property insurance the following objectives can be offered: to investigate in more detail the historical experience of formation of the system of insurance protection of individuals’ and legal entities’ property; identify the characteristics and trends of property insurance in Ukraine insurance market in recent years and forecast for the further development; explore the range of services on property insurance offered by the Ukrainian insurers and new offerings.